2019
DOI: 10.3390/mi10080548
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Lab-on-a-Chip Platform for Chemical Stimulation and Parallel Analysis of Ion Channel Function

Abstract: Functional imaging has been a widely established method for the assessment of ion channel function in vitro. Conventional infrastructure used for in vitro functional analysis of ion channels is typically proprietary, non-customizable, expensive, and requires a high level of skill to use and maintain. 3D desktop printing, which is employed in the rapid prototyping field, allows for quick engineering of alternatives to conventional imaging infrastructure that are customizable, low cost, and user friendly. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Our work establishes a strategy to design circuits that spontaneously break detailed balance to guide and accumulate active matter, enforced by robust out-of-equilibrium topological phenomena. This design strategy and the 3D printing capabilities, permit to envision 3D extensions where the accumulation of particles is guaranteed by non-planar surfaces (e.g., using ramps, or different levels) 55 or by implementing dynamic topographical pathways topology 56 .…”
Section: Resultsmentioning
confidence: 99%
“…Our work establishes a strategy to design circuits that spontaneously break detailed balance to guide and accumulate active matter, enforced by robust out-of-equilibrium topological phenomena. This design strategy and the 3D printing capabilities, permit to envision 3D extensions where the accumulation of particles is guaranteed by non-planar surfaces (e.g., using ramps, or different levels) 55 or by implementing dynamic topographical pathways topology 56 .…”
Section: Resultsmentioning
confidence: 99%
“…Using cell morphology imaging during chemical stimulation with capsaicin, the fluorescence intensity showed a consistent increase with an increase in the intracellular calcium concentration. The authors concluded that the model was reliable for ion analysis [63].…”
Section: Analysis Of Drugs In Kidney-on-chip Devicesmentioning
confidence: 98%
“…An interesting device was also realized by Aschenbrenner et al [ 102 ], who employed 3D printing of acrylonitrile butadiene styrene to create ultra-low-cost microfluidic platforms. The design is made of two 3D printed parts, namely the main compartment and an outlet connector for drainage tubing ( Figure 29 ).…”
Section: Geometriesmentioning
confidence: 99%
“…The green color inside the cell chamber indicates a mixing ration of approximately 0.5, and thus demonstrates homogeneous distribution of efficiently mixed solutions. Reprinted from an open-access source [ 102 ].…”
Section: Figurementioning
confidence: 99%